Last Generation Mechatronics: a Two-level Platform-based Reconfigurable Technology Approach - Szász, Csaba (Recent Innovations in Mechatronics, 2018)
As is well known mechatronic systems currently being designed and developed are often difficult multidisciplinary undertakings. Based on the intrinsic coupling of different implementation technologies, efficient design of mechatronic systems is of primordial importance for development of next generation industrial products. This paper is focused to current and future technological trends aimed to improve the design and implementation processes of mechatronic systems in an increasingly harsh industrial environment. Special attention is dedicated to introduction of the two-level platform-based reconfigurable technology approach. This strategy efficiently combines major advantages of both the hardware and software platform-based development trends in modern mecatronic systems. In order to support the unfolded theoretical arguments a last generation and versatile mechatronic system development is presented and discussed in the paper. The mentioned trends can be used as rough orientation for future mechatronic systems research and implementation activities.